Reference intervals of complete blood count and coagulation tests in Vietnamese pregnant women - Huan Nguyen Pham; Nghiem Xuan Huynh; Phuc Nguyen Huu Pham; Dung Ngoc Yen Dang; Long Thang Cao; Diem Minh Huynh; Hau Thi Thu Thoi; Oanh Hoang Le; Suzanne Monivong Cheanh Beaupha (BMC, 2023)
Abstract Background Pregnancy has major effects that make hematology parameters outside of normal reference ranges. Therefore, we conducted this study to establish reference intervals for Vietnamese pregnant women. Methods From June 2023 to Augst 2023, blood samples from 879 eligible pregnant women were run on DxH 900 hematology analyzer and ACL TOP 550 coagulation analyzer. The tested parameters are prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen (FIB), white blood cell (WBC) and its differentials (neutrophils, lymphocytes, monocytes, eosinophils and basophils), red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), RBC distribution width (RDW), RBC distribution width standard deviation (RDW-SD), platelet count (PLT), mean platelet volume (MPV). A non-parametric method was used to establish the 2.5th and 97.5th percentile reference intervals. Results PT, APTT decrease but fibrinogen increases during pregnancy. Physiological adaptations of pregnancy result in a decrease in RBC count, but an increase in WBC count and no changes in platelet count. The reference intervals for PT (seconds), APTT (seconds), fibrinogen (mg/dL), in the first trimester were 10.30-12.88, 25.40-35.46, 280.28-559.00, in the second trimester were 9.80-11.66, 24.05-33.23, 347.75-593.35, in the third trimester were 9.60-11.40, 23.40-31.80, 330.28-628.56, respectively. The reference intervals for main hematology parameters which are WBC (× 109/L), RBC (× 1012/L), HGB (g/dL), HCT (%), PLT (× 109/L) in the first trimester were 6.33-15.24, 3.73-5.32, 10.33-13.95, 32.22-42.29, 169.66-413.88, in the second trimester were 6.99-15.55, 3.33-4.98, 9.71-13.17, 30.26-40.07, 172.34-372.19, in the third trimester were 6.22-14.14, 3.54-4.98, 9.80-13.97, 31.11-42.70, 151.30-417.14, respectively. Conclusions Most established referenced intervals from each trimester differ from other trimesters. These trimester-specific reference ranges for Vietnamese pregnant women will aid clinicians in entepreting parameters and help other laboratories adopt these ranges after validating. Trial registration This study is registered at www.clinicaltrials.gov as NCT05929326.